Janus nanoparticles for T cell activation: clustering ligands to enhance stimulation. Issue 23 (2nd March 2017) - Lee, Kwahun; Yu, Yan
Abstract : Janus nanoparticles displaying clustered ligands enhance T cell activation by increasing the local surface density of ligand stimuli. Abstract : The in vitro activation of T cells by synthetic particles is a promising technique for adoptive cancer immunotherapy. While it is known that cell-surface receptors form clusters during T cell activation, the use of clustered ligands on synthetic particles to modulate T cell response is a largely unexplored concept. Building upon our previous finding that T cells respond differently to various micro-sized patterns of ligands, we here investigate the effect of nano-sized ligand clusters on T cell activation. Two-faced Janus nanoparticles were fabricated to display ligands of different functions in spatially segregated clusters on single nanoparticles. Going beyond our earlier qualitative study, here we precisely quantified and controlled the surface density and the total amount of ligands on single nanoparticles. We show that nanoparticles with clustered ligands activate T cells to a greater level than the ones uniformly coated with the same number of ligands. The enhanced effect is due to the increased local surface density of ligands. The results demonstrate that the spatial arrangement of ligands on particles influences the activation response of T cells and may be used as a new strategy to increase T cell stimulation in the presence of an insufficient amount of stimuli. This fundamental study also represents an initial step in using nanoscale Janus particles for manipulating immune cell responses.